2021
DOI: 10.1111/njb.03008
|View full text |Cite
|
Sign up to set email alerts
|

Strong gene flow explains lack of mating system variation in the perennial herb, Vincetoxicum hirundinaria, in a fragmented landscape

Abstract: Fragmented landscapes may have implications for the genetic structure of populations and for the microevolution of plant species. In particular, landscape fragmentation and/or population isolation might affect the evolution of plant mating systems. Here, we study the consequences of landscape fragmentation on the genetic structure of populations of a perennial herb, Vincetoxicum hirundinaria with a mixed mating system. Our study area, the south‐western Finnish archipelago, was formed after the glacial ice shee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 88 publications
(107 reference statements)
0
3
0
Order By: Relevance
“…Howover, a gene exchange/flow can provide beneficial genetic variation and may facilitate adaptation to environmental change (Li et al, 2021b;Wood et al, 2021). This is because that gene flow is expected to increase heterozygosity and reintroduce variation that can allow for masking or purging of fixed deleterious alleles (Ferrer et al, 2021;Muola et al, 2021). Unexpected, the OTc group (central populations) of O. taihangensis presented a slightly lower genetic diversity than that of OTd group (marginal populations) (Table 1).…”
Section: Landscape Features Affect Genetic Characteristics Of Opistho...mentioning
confidence: 98%
“…Howover, a gene exchange/flow can provide beneficial genetic variation and may facilitate adaptation to environmental change (Li et al, 2021b;Wood et al, 2021). This is because that gene flow is expected to increase heterozygosity and reintroduce variation that can allow for masking or purging of fixed deleterious alleles (Ferrer et al, 2021;Muola et al, 2021). Unexpected, the OTc group (central populations) of O. taihangensis presented a slightly lower genetic diversity than that of OTd group (marginal populations) (Table 1).…”
Section: Landscape Features Affect Genetic Characteristics Of Opistho...mentioning
confidence: 98%
“…These differences were not observed in an analysis including only self-fertile individuals. A field study in Finland found that V. hirundinaria reproduces primarily by outcrossing, perhaps due to inbreeding depression among the offspring of self-pollinated plants (Muola et al 2021). Evidence for inbreeding depression in V. hirundinaria is mixed, partially due to substantial methodological differences between studies (Leimu 2004; Leimu and Mutikainen 2005; Muola et al 2011).…”
Section: Reproductionmentioning
confidence: 99%
“…Much of the northernmost part of our study area was submerged and has gradually risen above the sea level during the last 7000 years (Harff & Meyer, 2011 ; Karlsson, 2007 ). This process has affected plant spread (Muola et al, 2021 ) with likely effects on the geographic structuring of gall midge populations.…”
Section: Introductionmentioning
confidence: 99%